United State experience in management of science and technology activities funded by foundations and some suggestions for Vietnam - Kiet, Tan (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
Scientific and technological (S&T) activities in the United States are not organized and managed by government administrative bodies, they are conducted and managed by research units in universities, R&D institutes and companies. The State just plays advisory and supportive role and not directly involved in S&T management. S&T activities and human resource development are always associated with each other. Research institutions not only create favorable conditions for scientists to generate innovations and creativity in a cooperative and competitive environment but also ensure the protection of rights and obligations of the research team by leading scientists. Lessons learnt from the USA show that beneficiaries of the foundations’ support must be enterprises or research institutions operating as autonomy, self-reliance and self-financed entities. From the US experience in the organization of S&T system and establishment of mechanisms for S&T management, this paper provides a different approach in building S&T management capacity of the country in immediate and long-term perspective. Code: 13071001 <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">